Teachers’ Strategies in Managing English Classrooms for Active Learning - Zainuddin (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study examines teachers’ strategies in managing English classrooms to promote active learning. Effective classroom management is essential in English language teaching, as it supports student engagement, interaction, and meaningful language use. A qualitative descriptive research design was employed to explore how teachers organize classroom activities, manage interactions, and address challenges in implementing active learning. The participants of this study were English teachers selected through purposive sampling based on their teaching experience and involvement in interactive learning practices. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques, with triangulation applied to ensure the trustworthiness of the findings. The results indicate that teachers employed various strategies to facilitate active learning, including establishing clear classroom rules and routines, organizing pair and group work, managing instructional time effectively, and fostering positive teacher–student relationships. These strategies were found to enhance student participation, confidence, and engagement in English learning activities. However, challenges such as large class sizes, mixed proficiency levels, and limited resources were also identified. Despite these challenges, teachers demonstrated adaptability by modifying classroom management practices to sustain active learning. In conclusion, effective classroom management strategies are crucial in supporting active learning in English classrooms. The findings of this study provide practical insights for English teachers and educational institutions in improving classroom management practices to enhance students’ English learning experiences.